Analysis of Buying and Selling Practices Online in Islamic Law Perspective - Mutiara Shifa (Journal Research of Social Science, Economics, and Management, 2021)
Economic behavior has been formed since humans began to need other individuals who have goods or services that they do not have. The form of buying and selling has developed following society and social changes. Advancements in communication and information have impacted progress in the business world. Long-distance buying and selling have become a prevailing habit in today's business world. Feel disadvantaged because the goods received do not match the picture or the goods received also turn out to be defective or the goods do not arrive at the buyer, and many other cases. Islamic law itself has regulated this buying and selling activity quite strictly, both in the arguments of Al -Qur'an, Hadith, Ijma', and also Qiyas. The purpose of this study was to determine whether the practice of buying and selling online is according to Islamic Law. This study uses descriptive qualitative research methods. The results found that buying and selling online is allowed as long as the goods or products being traded follow the specifications or characteristics of the goods that have been determined. Moreover, the type and nature of the goods to be bought are known. Islam is consensual. There is no coercion from any party to buy an item. If the buying and selling transaction online does not follow the provisions of Islamic law, which has established the terms of the contract and buying and selling, the online buying and selling transaction is unlawful or invalid.